Gradual degradation in InAs quantum dot lasers on Si and GaAs - Hughes, Eamonn T.; Shang, Chen; Selvidge, Jennifer; Jung, Daehwan; Wan, Yating; Herrick, Robert W.; Bowers, John E.; Mukherjee, Kunal (Royal Society of Chemistry, 2024)
Reliable quantum dot lasers on silicon are a key remaining challenge to successful integrated silicon photonics. In this work, quantum dot (QD) lasers on silicon with and without misfit dislocation trapping layers are aged for 12 000 hours and are compared to QD lasers on native GaAs aged for 8400 hours. The non-trapping-layer (TL) laser on silicon degrades heavily during this time, but much more modest gradual degradation is observed for the other two devices. Electroluminescence imaging reveals relatively uniform gradual dimming for the aged TL laser on silicon. At the same time, we find nanoscale dislocation loop defects throughout the quantum dot-based active region of all three aged lasers via electron microscopy. The Burgers vector of these loops is consistent with . We suggest that the primary source of degradation, however, is the generation and migration of point defects that substantially enhance non-radiative recombination in the active region, the visible symptom of which is the formation of dislocation loops. To prevent this, we propose that laser fabrication should be switched from deeply etched to shallow etch ridges where the active region remains intact near the mesa. Additionally, post-growth annealing and altered growth conditions in the active region should be explored to minimize the grown-in point defect density. After extended aging, InAs quantum dot lasers form dislocation loops in the active region due to the coalescence of point defects. The point-defect formation process drives gradual laser degradation and is a key impediment to long-life lasers.